Tingkat Kesiapsiagaan Siswa SDN 9 Banda Sakti dan SD Sukma Bangsa dalam Mengantisipasi Bencana Gempa Bumi - Dila Khairunnisa Mahira Zulmay; Wheny Utariningsih; Maulana Ikhsan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The geographical location of Indonesia, which consists of islands and is located between the meeting of the earth's plates, causes catastrophic events, such as earthquakes. Lhokseumawe is located in the province of Aceh which is a disaster-prone area because of its geological location. Lhokseumawe has a high potential for earthquake hazards. In disaster situations, education services are often not the main concern even though education is the social sector that is most affected by disasters. Therefore, a high level of preparedness is needed for school students, especially elementary school students who are classified as vulnerable groups to the impact of disasters. The purpose of this research was to determine the level of preparedness of elementary school students in dealing with earthquake disasters. The type of this research is a descriptive with a cross sectional approach. The sampling technique used stratified random sampling with 117 students as respondents..The.results.showed.that.the.level.of.preparedness.of.elementary school students at SDN 9 Banda Sakti and SD Sukma Bangsa Lhokseumawe City in dealing with earthquake disasters was in the moderate category with a frequency of 61 students (52.1%) which included four indicators, namely knowledge about disasters in the medium category with a frequency of 48. students (41%), emergency response plans are in the high category with a frequency of 71 students (60.7%), disaster warning systems are in the low category with a frequency of 55 students (47%), and resource mobilization is in the low category with a frequency of 52 students (44.4%).